2021
DOI: 10.3389/fimmu.2021.743022
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of COVID-19 on the Placenta During Pregnancy

Abstract: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic. The virus primarily affects the lungs where it induces respiratory distress syndrome ranging from mild to acute, however, there is a growing body of evidence supporting its negative effects on other system organs that also carry the ACE2 receptor, such as the placenta. The majority of newborns delivered from SARS-CoV-2 positive mothers test negative following delivery, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 131 publications
(136 reference statements)
3
46
0
Order By: Relevance
“…This finding is of importance not only in this model of PE, but also during human PE where levels of Gas6 have been found to be increased in the plasma of the preeclamptic mother [ 6 ]. Although studies of lungs during PE are scarce, recent reports have shown that pregnant women infected by the virus COVID-19 (which mostly affects the lungs) have increased lung inflammation and this correlates with obstetric complications such as miscarriages, restricted fetal growth, and most relevant to our studies, the development of PE-like symptoms [ 48 , 49 , 50 ]. This also correlates with increased serum Gas6 and increased lung AXL in patients affected by this virus [ 51 ].…”
Section: Discussionmentioning
confidence: 95%
“…This finding is of importance not only in this model of PE, but also during human PE where levels of Gas6 have been found to be increased in the plasma of the preeclamptic mother [ 6 ]. Although studies of lungs during PE are scarce, recent reports have shown that pregnant women infected by the virus COVID-19 (which mostly affects the lungs) have increased lung inflammation and this correlates with obstetric complications such as miscarriages, restricted fetal growth, and most relevant to our studies, the development of PE-like symptoms [ 48 , 49 , 50 ]. This also correlates with increased serum Gas6 and increased lung AXL in patients affected by this virus [ 51 ].…”
Section: Discussionmentioning
confidence: 95%
“…Examination of placentas infected with SARS-CoV-2 from stillborn fetuses has been enlightening, significantly adding to the understanding of the mechanism(s) for intrauterine fetal demise. These studies have largely been made possible by the development of techniques for the tissue localization of SARS-CoV-2 in the placenta including immunohistochemistry to detect viral antigens and RNA in situ hybridization to identify viral nucleic acid [ 25 , 42 , 77 ] ( Figure 6 ). Unfortunately, in the large majority of these cases the specific strain of SARS-CoV-2 was not identified.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%
“…These changes can cause a difference in the maternal immune response to infections during pregnancy, particularly to SARS-CoV-2 [ 2 ]. During gestation, maternal levels of natural killer (NK) cells decrease [ 3 ]. NK cells are innate immune cells that are known to have cytotoxic activity against virally infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pregnant woman’s ability to protect herself from viral infections is attenuated. Additionally, NK cells are reduced during infection with SARS-CoV-2 infection [ 3 ]. As a result, a COVID-19-positive gravid patient is at risk for acquiring additional respiratory viral infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation